Nothogreniera new genus, for two species of Australian "Paracnephia" (Diptera: Simuliidae) - Craig, Douglas A.; Currie, Douglas C.; Moulton, John K. (Zootaxa, 2018)
Two species of Australian Simuliidae known only from adult females and currently assigned to "Paracnephia" are re-described, as are their now-known males and immature stages. Morphological character states of "Paracnephia" fergusoni (Tonnoir) and "P." fergusoni var. (Mackerras & Mackerras) reveal that they are markedly distinct from all other Australian species, and are here assigned to the new genus—Nothogreniera—the most plesiomorphic Gondwanan Australian simuliid. Structural variation among populations of N. fergusoni suggests that this entity comprises a species complex.